Mechanical and dielectric properties of direct ink writing Si2N2O composites. Issue 4 (April 2021) - Jin, Haize; Jia, Dechang; Yang, Zhihua; Zhou, Yu
Abstract: Si2 N2 O composites were achieved via direct ink writing technique and pressureless sintering. The design and optimization of inks and the effect of mass ratio of Si3 N4 and SiO2 on the phase composition, microstructure, mechanical properties and dielectric properties of composites were systematically investigated. The inks exhibit superior stability and printability. Increasing SiO2 content facilitated densification and enhancement of mechanical property. The generation of β-Si3 N4 and Si2 N2 O and the nucleation of cristobalite were restrained by high content SiO2 . The ceramic composites with the flexural strengths from 74.1MPa to 104.9MPa and low dielectric constant (≤4.68) were fabricated. This strategy provides a systematic reference for synthesis of high-performance porous Si2 N2 O composites based on the DIW.